Improving Learning Outcomes of Grade VII Students.B SMP Negeri 3 Kendari on Addition and Subtraction Materials Algebraic Forms Through the Use of Props - Aksaruddin (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2022)
The purpose of the study was to determine the increase in teacher and student activities in teaching and learning activities and increase student learning outcomes after participating in mathematics learning with the subject matter of adding and subtracting algebraic forms through teaching aids. The subjects who were subject to action were class VII.B SMP Negeri 3 Kendari in the first semester of the 2019/2020 school year, totaling 36 students, consisting of 13 boys and 23 girls. This research was only carried out in one cycle because the activities of teachers and students, as well as student learning outcomes, had met the criteria of completeness that had been previously set, namely, 80% of teacher and student activities met the criteria of good and very good, so it was said to be complete, and 80% of students got a score of 65 or absorption. 65% and above, then the learning outcomes criteria are complete. The teacher's activities were obtained from 10 aspects observed: 6 (60%) achieved excellent standards, 4 (40%) reached good criteria, and 0(0%) were sufficient and less. This data shows that the activities carried out by the teacher are all complete because the requirements are good and very good (100%). The student activities obtained from the seven aspects observed in this action research were 665 (95.29%) achieving perfect criteria, 19 (2.71%) fulfilling good criteria, 0 (0%) sufficient criteria, and 14 (2%) ) got fewer criteria. These data indicate that the student activities have been completed because the requirements are good and very good (98%). Student learning outcomes in the addition and subtraction of algebraic forms from 36 students 80.5% obtained a score of 65 or absorption power of 65% and above. These data indicate that the learning outcomes have been completed.